Improved Zika virus plaque assay using Vero/TMPRSS2 cell line - Olukunle O. Oluwasemowo; Monica E. Graham; Deepa K. Murugesh; Monica K. Borucki (Microbiology Spectrum)
ABSTRACT Plaque assay is the gold standard for the quantification of viable cytopathic viruses like Zika virus (ZIKV). Some strains of ZIKV produce plaques that are very difficult to accurately visualize and count on the commonly used Vero cell line. From data generated in our lab, we became curious if Vero/TMPRSS2 cells may be a better alternative; therefore, we compared the plaque forming units of two strains of ZIKV on Vero/TMPRSS2 cells to those produced by Vero cells. We also compared the virus stock titer generated on Vero/TMPRSS2 cells to that generated by the Vero cell line. Although the Vero cells generated higher quantity of ZIKV stocks, the Vero/TMPRSS2 cells produced plaques with significantly improved morphology and visibility and may, therefore, be a better alternative to use for performing plaque assays for strains of ZIKV that are more difficult to titer on regular Vero cells.IMPORTANCEWhile there are several methods of viral quantification, the plaque assay remains the gold standard for accurate quantification of replication-competent, cytopathic viruses including Zika virus (ZIKV). Vero cells are commonly used to titer ZIKV stock via the plaque assay. Prior to the initiation of this study, we observed that ZIKV-PRV strain plaque assays using Vero cells often yielded plaques that were very small, overly diffuse, and hard to count. We also observed that the ZIKV-CAM strain often did not produce plaques at all on Vero cells. This study shows that Vero cells expressing TMPRSS2 improve the morphology and visibility of plaques produced by ZIKV-PRV and ZIKV-CAM compared to regular Vero cells and may, therefore, be a better alternative to use for performing plaque assays for these strains and perhaps for other strains of ZIKV that are difficult to titer. However, Vero cells proved to be superior for generating high titer stock.